1999
DOI: 10.1046/j.1525-1373.1999.d01-4.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Ultrastructural Imaging of Macrophages Using a Novel X‐Ray Contact Microscopy

Abstract: A compact, high-resolution, laser-plasma, x-ray contact microscopy method using a table-top Nd:glass laser system has been developed. This x-ray microscopy system was applied for the observation of macrophage ultrastructures. These images were produced using proximity imaging in which a 5-ns pulse of soft x-rays with wavelengths near and inside the water windows (23A-44A) produced by the laser-plasma were absorbed by the specimen and then registered on a photo resist. The x-ray images imprinted on the photo re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In collaboration with the Center for Research and Education in Optics and Lasers at the University of Central Florida (Orlando, FL) we performed a pilot study to test the ultramicrography technique described above to obtain highresolution images of E. coli, other bacteria, and macromolecules (Kado et al, 1996;Rajyaguru et al, 1995;1996a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In collaboration with the Center for Research and Education in Optics and Lasers at the University of Central Florida (Orlando, FL) we performed a pilot study to test the ultramicrography technique described above to obtain highresolution images of E. coli, other bacteria, and macromolecules (Kado et al, 1996;Rajyaguru et al, 1995;1996a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The visualization of dry or hydrated human macrophages and Leydig cells demonstrated that SXCM allows the morphologies of actual intact cells to be viewed and encourages further technological development for biomedical research [45,51,[60][61][62]. This technique also offered the possibility of monitoring the morphological changes in microorganisms (e.g., upon exposure to antibiotics), as was demonstrated for the Gram-negative bacterium, Pseudomonas aeruginosa, and Candida albicans, a yeast, among others [63,64].…”
Section: Cell Imaging With Sxcmmentioning
confidence: 78%
“…Most of the works observing biological specimens with laser plasma x-ray have been done with contact xray microscopy, which is the indirect imaging placing biological specimens onto PMMA photo resist and observing the developed photo resist after exposure with x-ray pulse. Biological cells, bacteria, and other biological specimens have been observed [1][2][3].…”
Section: Introductionmentioning
confidence: 99%